2018
DOI: 10.7759/cureus.2116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes Mellitus Among Urban Bihari Communities in Dhaka, Bangladesh: A Cross-sectional Study in a Minor Ethnic Group

Abstract: IntroductionThe prevalence, disease progression, and treatment outcomes for patients with type 2 diabetes vary significantly between ethnic groups. The Bihari community constitutes one of the most vulnerable populations in Bangladesh on the basis of access to health services and other fundamental rights. Our study aimed at finding out the prevalence and risk factors of type 2 diabetes among the Bihari adults in Dhaka city.MethodsThis cross-sectional community-based study was carried out among stranded Pakistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The alcohol consumption rate was negligible among this study population which is similar with the Bihari's of Mirpur and underprivileged population of Shanty town. 11,15 We found the alcohol consumption rate is even noticeably less than the native Indian Bihari population. 17 Low alcohol consumption scenario in Bangladesh is actually the reflection of the successful restriction on alcohol production, business and consumption whereas Bangladeshi society, culture, religion and law are playing a favourable role.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The alcohol consumption rate was negligible among this study population which is similar with the Bihari's of Mirpur and underprivileged population of Shanty town. 11,15 We found the alcohol consumption rate is even noticeably less than the native Indian Bihari population. 17 Low alcohol consumption scenario in Bangladesh is actually the reflection of the successful restriction on alcohol production, business and consumption whereas Bangladeshi society, culture, religion and law are playing a favourable role.…”
Section: Discussionmentioning
confidence: 69%
“…Prevalence of overall tobacco use was found less among the Bihari population of this study than the available relevant studies in Bangladesh including two national surveys. 11,[13][14][15] Previous study among the Bihari's in Mirpur camp of Dhaka city reported noticeably higher proportion of smoking tobacco use alone. 11 The recent Global Adult Tobacco Survey reported almost constant finding for tobacco use with our study whereas data from WHO STEPS Survey and another study conducted to identify NCD risk factors among an underprivileged population in Dhaka reported noticeably higher prevalence of tobacco users.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Around 85% population of age group 25-65 never checks for diabetes [7]. A recent study by British Medical Journal says, 1 in 10 Bangladeshi adults aged ≥18 years have hyperglycemia (among urban residents) [8]. Even in rural Bangladeshi community, undiagnosed diabetes was high, 7.2% found in a 2016 and 10% in 2019 [9,10].…”
mentioning
confidence: 99%